Penggunaan Kredit Sindikasi untuk Pendanaan Proyek Infrastruktur Ketenagalistrikan pada PT PLN (Persero) - Isnan, Fadillah; Randi Sulistiyono, Dwi; Ramadhian, Fitrah (Technology and Economics Law Journal, 2025)
The Indonesian government continues to strive to develop infrastructure, including electrical infrastructure, which serves as the main driver and foundation of the economy. The task of managing the electricity sector is entrusted to the state through state-owned enterprises, with PT PLN (Persero) as the main implementer. The planning for these electricity infrastructure projects has been outlined in the 2021-2030 Electricity Supply Business Plan (RUPTL). To support the realization of these projects, substantial funding is required, one of which is through a syndicated loan scheme. Syndicated loans, which involve a number of financial institutions, offer organized and efficient financing solutions with proportionally shared risks. This scheme has become a major financing alternative to support infrastructure projects and other strategic sectors in Indonesia, providing a significant impact on sustainable economic growth.